Knowledge, Attitude, and Perception of Learners Towards the Use of ChatGPT in the University of Ibadan, Nigeria - Omotayo Ifesewa Shittu; Dauda Aderemi Busari; Olawale Yinusa Olonade (International Journal of Sociology of Education)
ChatGPT has acquired a global audience due to its widespread integration into educational practices and the rapid advancement of technology, particularly in the innovative artificial intelligence tool. Hence, a growing need exists to understand how students interact with and perceive such writing tools within the academic landscape. This study aims to provide valuable insights into integrating AI technologies into higher education. The study used a mixed-method approach guided by the social constructivism theory. Through the multi-stage sampling, 402 students were selected for quantitative analysis, while qualitative insights were gathered through ten (10) In-depth interviews with the University academics. Quantitative data was analysed using descriptive statistics and the Independence Sample T-test in IBM-SPSS Version 23. Qualitative data underwent thematic and content analysis. The study findings indicate a high level of awareness among students on ChatGPT, with most obtaining knowledge about the tool from recommendations by friends and colleagues. Despite its high level of awareness among students, the study found that some academics reported a lack of familiarity with ChatGPT. Based on the findings, several recommendations are proposed, which include organising seminars on technology, specifically AI, for lecturers and students and integrating them into the curriculum to create awareness.